Vagal sensory neurons and gut-brain signaling - Yu, Chuyue D. (Curr Opin Neurobiol, 2020)
Our understanding of the gut system has been revolutionized over the past decade, in particular regarding its role in immune control and psychological regulation. The vagus nerve is a critical link between gut and brain, transmitting diverse gut-derived signals, and has been implicated in many gastrointestinal, neurological, and immunological disorders. Using state-of-the-art technologies including single-cell genomic analysis, real-time neural activity recording, trans-synaptic tracing, and electron microscopy, novel physiological functions of vagal gut afferents have been uncovered and new gut-to-brain pathways haven been revealed. Here, we review the most recent findings on vagal sensory neurons and the gut-brain signaling, focusing on the anatomical basis and the underlying molecular and cellular mechanisms. Such new discoveries explain some of the old puzzling problems and also raise new questions in this exciting and rapidly growing field.